O que é ser policial militar?: Percepções de integrantes da polícia militar da Paraíba sobre o "militarismo" na instituição - Costa, Davisson Henrique Araújo da (2016)
The current social situation is characterized by a significant increase in crime rates, demanding an increasingly effective operation of the agencies responsible for public security. In this context, the military police are seen by the media and by human rights organizations as one of the institutions that are most responsible for violating fundamental rights. Experts argue that one of the causes of such violations is the militarization of the police and the consequent authoritarianism present in their practices, which reveals the need to investigate this phenomenon. Therefore, to effectively understand the institution, it is necessary also to know the views of its members. In this sense, this research investigates the perceptions of military policemen of Paraíba about what is militarism for them and for the organization. It is discussed, then, the existing duality between militarism maintenance discourse and the demilitarization discourse, in order to identify and relate to each other perceptions and positions of the military policemen about the role of militarism for the institution, its positive and negative aspects. Thus, the study was characterized as a field research and documentary research of qualitative nature, being conducted semi-structured interviews with thirty military police. Based on the literature that addresses the issue, it broke the hypothesis that the military police, for the most part, which is composed mainly of soldiers, they see militarism as an inadequate model for the effective performance of the public safety services, since it is filled with relations of domination that prevent the configuration of a truly citizen police. As a result, the hypothesis was confirmed, and also was revealed a clear distinction between the ways of seeing the militarism of the soldiers and the officers. The soldiers reject the militarism widely while the officers only suggest an adaptation of the organization to democratic context without, however, removing the militarized structure.